Теоретичні засади проблеми розвитку баянного виконавства на Харківщині - Снєдкова Людмила; Snedкova Lyudmila (Видавництво «Код», 2025)
Резюме. У статті порушується питання розвитку харківської академічної народноінструментальної школи, що відбувався в царині загальноукраїнських мистецьких процесів. Зокрема, історико-виконавський досвід митців Слобожанщини спирався на: творчість харківських композиторів; здобутки в науково-дослідній роботі; методико-педагогічну діяльність викладачів вищих та середніх мистецьких навчальних закладів. З’ясовано, що ці чинники визначили теоретичні засади для вивчення процесу розвитку та становлення усіх форм ансамблевого виконавства за участю баяна та акордеона Харківщині.

Abstract. The article raises the issue of the development of the Kharkiv academic folk instrumental school, which took place in the field of all-Ukrainian artistic processes. In particular, the historical and performing experience of the artists of Slobozhanshchyna was based on: the work of Kharkiv composers; achievements in scientific research; methodological and pedagogical activities of teachers of higher and secondary art educational institutions. It was found that these factors determined the theoretical principles for studying the process of development and formation of all forms of ensemble performance with the participation of bayan and accordion in Kharkiv region. Analysis of scientific literature revealed that the pedagogical and educational activities of Kharkiv educational music institutions (Kharkiv Music College named after B. Lyatoshynsky, Kharkiv National University of Arts named after I. P. Kotlyarevsky), which have been operating for more than one hundred and twenty years, provide grounds for stating the fact of the existence of the Slobozhansk school with its creative features, outstanding performers, laureates of national and international competitions, and scientists.
Theoretical principles of the problem of the development of bayaan performance in Kharkiv regio
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: ансамблево-інструментальне музикування за участю баяна та акордеона на теренах Слобожанщини; баянне виконавство; розвиток та становлення